Preservation of Carrion Flowers as an Ecotourism Attraction in Bogor Botanical Garden - Pradini, Gagih; Kusumaningrum, Anisa Putri; Agustiani, Fitri; Ardira, Maya Ayu; Waluyo, Tri (CV ODIS, 2023)
In Bogor City, there is a large botanical garden that can help us learn about various kinds of trees and plants in the world called